2017
DOI: 10.1007/s10670-017-9904-4
|View full text |Cite
|
Sign up to set email alerts
|

Intuition Talk is Not Methodologically Cheap: Empirically Testing the “Received Wisdom” About Armchair Philosophy

Abstract: The "received wisdom" in contemporary analytic philosophy is that intuition talk is a fairly recent phenomenon, dating back to the 1960s. In this paper, we set out to test two interpretations of this "received wisdom." The first is that intuition talk is just talk, without any methodological significance. The second is that intuition talk is methodologically significant; it shows that analytic philosophers appeal to intuition. We present empirical and contextual evidence, systematically mined from the JSTOR co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…11 For another example of applying the methods of data science to philosophy, see Ashton and Mizrahi (2017).…”
Section: Discussionmentioning
confidence: 99%
“…11 For another example of applying the methods of data science to philosophy, see Ashton and Mizrahi (2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Andow (2015a) notes a significant increase in the use of intuition talk in academia and, particularly, in analytic philosophy: "the proportion of philosophy articles indexed in JSTOR indulging in intuition talk has grown from around 22 percent in the decade 1900-1909 to around 54 percent in the decade 2000-2009" (Andow 2015a: 190). In this same vein, Ashton and Mizrahi (2018) showed that analytic philosophers had begun to use intuition talk much earlier than in the 1940s. They did a search using the JSTOR corpus and the HathiTrust database, which allowed them to conclude that "intuition talk goes all the way to the 1800s" (Ashton, Mizrahi 2018: 599).…”
Section: The Argument From "Intuition" Talkmentioning
confidence: 98%
“…Finally, there is a fourth line of response, which is to point to empirical findings on philosophers' use of intuitions over time. In a recent paper, Ashton & Mizrahi (2018), building on the methodology of Andow (2015), examine the use of intuitions in philosophy publications from two major databases (JSTOR and HathiTrust). Their findings stand in stark contrast to the idea that the intuition-centric philosophy is an historical relic; far from peaking in (say) the 1960s, the proportion of philosophy publications containing intuition talk (i.e., use of the word 'intuition' and its cognates) has grown with each successive decade, with the highest proportion being found in the decade from 2000-2009 (the most recent decade studied) and the second-highest in 1990-1999.…”
Section: Intuitions Theories and The Mocmentioning
confidence: 99%